2018
DOI: 10.1108/jarhe-12-2017-0164
|View full text |Cite
|
Sign up to set email alerts
|

Affect vs cognition as antecedents of selection behaviour of elective courses using fsQCA

Abstract: Purpose The purpose of this paper is to investigate students’ attitude based on affective, behavioural and cognitive components. It will ascertain whether there is a link between the three components of attitude, which leads the possible classification of the elective courses. Design/methodology/approach The current study considers the students of the International Business Administration Department from Rustaq College of Applied Sciences, Ministry of Higher Education, Sultanate of Oman, during the academic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 55 publications
0
7
0
1
Order By: Relevance
“…Among all hierarchies, cognitive–affect–behavior (CAB) (Ajzen, 1993; Holbrook, 1986) is the most widely used sequence because of its unidirectional flow (Liu et al , 2017), known as the standard learning hierarchy (Solomon et al , 2006). Moreover, the behavior is influenced by affective and cognitive components separately as well as jointly (Jain and Jain, 2018). It gives a vast opportunity to examine affect-, belief- and group-based attitudinal models to study the behavior (Herr, 1995).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Among all hierarchies, cognitive–affect–behavior (CAB) (Ajzen, 1993; Holbrook, 1986) is the most widely used sequence because of its unidirectional flow (Liu et al , 2017), known as the standard learning hierarchy (Solomon et al , 2006). Moreover, the behavior is influenced by affective and cognitive components separately as well as jointly (Jain and Jain, 2018). It gives a vast opportunity to examine affect-, belief- and group-based attitudinal models to study the behavior (Herr, 1995).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The first principle of the complexity theory, equifinality, asserts that multiple paths could lead to the same outcomes in many cases of social science (Jain & Jain, 2018). Using mainly regression-based analytical approaches, existing research found that several paths could lead to student smartphone use in learning settings.…”
Section: Three Conditions For Configurational Approachmentioning
confidence: 99%
“…Öğrenciler, akademik ya da günlük hayatla ilgili birçok karar alırlar. Bu kararlar aile, arkadaş, öğretmen, okul, önbilgiler ve deneyimler gibi birçok faktörden etkilenir (Jain & Jain, 2018). Seçmeli ders seçimi de öğrencilerin karar vermek zorunda oldukları konulardan birisidir.…”
Section: Sosyal Bilgiler Eğitiminde Seçmeli Ders Seçme Stratejileri G...unclassified
“…Students make many decisions related to their academic or daily life. These decisions are influenced by various factors such as family, friends, teachers, school, prior knowledge, and experiences (Jain & Jain, 2018). Choosing elective courses is one of the issues that students often find challenging and complex (Baruch, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation